Knowledge sharing mediates the relationship between nurses’ job well-being and innovative behavior: A cross-sectional study - Syahrir Syahrir; Dewi Nurhanifah; Cheristina Cheristina; Yunita Kristina (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Innovative behavior among nurses is essential for improving healthcare quality; however, its underlying mechanisms remain insufficiently understood. This study aimed to examine the relationship between nurses’ job well-being and innovative behavior, and to test the mediating role of knowledge sharing. Research Methodology: A quantitative cross-sectional study was conducted among 100 nurses selected using stratified random sampling from public and private hospitals. Data were collected using validated Likert-scale instruments measuring job well-being, knowledge sharing, and innovative behavior. Data analysis included descriptive statistics, Pearson correlation, and Structural Equation Modeling (SEM) to assess direct and indirect effects. Results: Job well-being was significantly associated with innovative behavior (β = 0.21; 95% CI: 0.08–0.34; p = 0.002) and knowledge sharing (β = 0.48; 95% CI: 0.35–0.61; p < 0.001). Knowledge sharing showed a strong effect on innovative behavior (β = 0.50; 95% CI: 0.36–0.64; p < 0.001). The indirect effect of job well-being on innovative behavior through knowledge sharing was significant (β = 0.24; 95% CI: 0.15–0.36; p < 0.001), indicating partial mediation. Conclusion: Knowledge sharing plays a critical mediating role in translating nurses’ job well-being into innovative behavior. Strengthening psychological well-being and institutionalizing knowledge-sharing practices are essential strategies to enhance innovation capacity in healthcare organizations.